2019
DOI: 10.1093/mnras/stz1509
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar diffusion in large Prandtl number turbulence

Abstract: We study the effects of ambipolar diffusion (AD) on hydromagnetic turbulence. We consider the regime of large magnetic Prandtl number, relevant to the interstellar medium. In most of the cases, we use the single fluid approximation where the drift velocity between charged and neutral particles is proportional to the Lorentz force. In two cases we also compare with the corresponding two-fluid model, where ionization and recombination are included in the continuity and momentum equations for the neutral and char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This is different from a full two-fluid model, where there are separate equations which describe the time evolution of neutrals and charges, so that there is no assumption about their collisional timescale. It has been shown that in many situations, the single fluid MHD (extended with ambipolar terms) and the full two-fluid treatment give very similar results (Brandenburg 2019;Popescu Braileanu 2020).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is different from a full two-fluid model, where there are separate equations which describe the time evolution of neutrals and charges, so that there is no assumption about their collisional timescale. It has been shown that in many situations, the single fluid MHD (extended with ambipolar terms) and the full two-fluid treatment give very similar results (Brandenburg 2019;Popescu Braileanu 2020).…”
Section: Introductionmentioning
confidence: 94%
“…It is the most important process of magnetic field decay in neutron stars (Jones 1987;Hoyos et al 2010;Sinha 2020). Ambipolar diffusion has significant effects on turbulence present in the interstellar medium (Brandenburg 2019) or as produced by the magnetorotational instability in weakly ionized disks (Bai & Stone 2011). In solar context, ambipolar diffusion has an important contribution in the chromosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the diffuse warm gas can be treated as a single entity in dynamo models, and we do not consider the effects of ambipolar diffusion on the magnetic field [e.g. 98].…”
Section: Boundary Conditions In Mean-field Modelsmentioning
confidence: 99%
“…Besides the nonlinear regime, XL16 also studied the kinematic dynamo at a large and small magnetic Prandtl number, and at different ionization fractions. They found new regimes of kinematic dynamo, including the transitional stage in a high-Prandtl number medium with the shift of the correlation length of magnetic fields from the resistive scale to the viscous scale, and the damping stage of dynamo in a weakly ionized medium (see also [22]). XL16 predictions on the dynamo behavior resulting from the weak coupling between neutrals and ions at a low ionization fraction have been numerical confirmed by the two-fluid dynamo simulation [32].…”
Section: Introductionmentioning
confidence: 97%
“…Most earlier theoretical studies on turbulent dynamo focused on its kinematic regime with negligible magnetic back reaction [15,16,17,18,19]. For the kinematic regime of dynamo, the dynamo growth of magnetic fields and the magnetic field structure are sensitive to the plasma parameters, including both the ionization fraction [17,20] and the magnetic Prandtl number [21,22]. For astrophysical settings involving large length scales and long timescales, the kinematic dynamo alone is insufficient to explain the dynamo evolution of magnetic fields and their dynamical roles in the multi-scale astrophysical processes.…”
Section: Introductionmentioning
confidence: 99%